Perception of State Civil Apparatus towards Income Tax Article 21: Maximum Four Tax Theory Approach - Adil, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: Taxpayer compliance is crucial for an effective tax system. However, unclear tax collection procedures can create multiple interpretations, reducing compliance. This study examines the perceptions of State Civil Apparatus (ASN) regarding the collection of Income Tax Article 21 (PPh 21) and its alignment with Adam Smith’s Four Maxim Taxation principles: equity, certainty, convenience, and efficiency. Research Design and Methodology: This qualitative descriptive study employs interviews as the primary data collection method. ASN taxpayers at the Mamajang Sub-district Office, Makassar City, were interviewed to assess their perceptions of PPH 21 collection procedures. Findings and Discussion: ASN perceives the progressive tax system as fair, withholding tax as convenient, and the legal framework as clear, ensuring certainty. Tax collection costs are minimal, supporting efficiency. Implications: Enhanced taxpayer education and socialization can improve compliance. Future studies should explore other taxpayer groups, such as BUMN, TNI, and POLRI employees, using quantitative methods for broader insights.